Lower-temperature sintering and optimization ratio of SiO2-TiO2-B2O3-ZnO glass ceramic coatings for energy efficient tile - Faisal Habib; Mahmuddin Mahmuddin; Muhammad Imam Arif (Jurnal Polimesin, 2026)
Conventional ceramic tile glazes typically require firing temperatures above 1180°C, leading to high energy consumption and production costs. Despite extensive studies on composition and crystallization, integrated optimization of oxide balance, crystallization kinetics, and energy efficiency at reduced temperatures remains limited. This study aims to develop and optimize SiO₂–TiO₂–B₂O₃–ZnO glass-ceramic coatings through a combined experimental and data-driven approach to achieve enhanced mechanical performance at lower sintering temperatures. A series of compositions were formulated using locally sourced raw materials and sintered at 1080–1160°C. The crystallization behavior was first characterized using Differential Scanning Calorimetry (DSC) and fitted with the Johnson–Mehl–Avrami–Kolmogorov (JMAK) kinetic model. Phase evolution and microstructure were examined through X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Mechanical and optical performance were evaluated via Vickers microhardness testing, gloss measurement, and bulk density analysis. Multivariate regression and energy-performance correlation analysis were conducted using MATLAB. The results demonstrate that increasing TiO₂ content promotes heterogeneous nucleation, lowering crystallization peak temperature from 785°C to 725°C and increasing enthalpy release from 48 to 64 J/g. The Avrami exponent (n = 1.75–1.95) indicates three-dimensional crystal growth with mixed nucleation mechanisms. Vickers hardness improved from 515 HV to 670 HV with increasing TiO₂ concentration, while gloss moderately decreased due to enhanced crystalline fraction. The optimal composition (55 mol% SiO₂, 8 mol% TiO₂, 2 mol% B₂O₃, 2 mol% ZnO) achieved 648 HV, 63 GU, and a 12% reduction in firing energy, demonstrating the feasibility of energy-efficient coating design.